2007
DOI: 10.1523/jneurosci.5024-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Amyloid Precursor Protein and Tau for the Study of Axonal Traffic Pathways

Abstract: We describe a procedure for quantifying the numbers of expressed fluorescent fusion proteins on vesicles transported in axons. The method can be used to estimate numbers of vesicle-anchored molecules moving in both anterograde and retrograde directions and is also applicable to cytosolic proteins. This is demonstrated using neurons (explanted retinal ganglion cells) transfected with yellow fluorescent protein-tagged amyloid precursor protein (APP-YFP) or cyan fluorescent protein-tau (CFP-tau). To calibrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Both mass spectrometry and Tricine-urea gel electrophoresis showed the normal predicted profile of A␤ peptides without any alterations before or after dimerization from both APP F1 and APP F2 constructs. These findings are consistent with the apparent normal processing of APP GFP fusions used by a number of laboratories (38,(41)(42)(43)(44)(45). However, with this approach, our results unequivocally showed that forced dimerization of APP lowered rather than increased A␤ generation.…”
Section: Discussionsupporting
confidence: 92%
“…Both mass spectrometry and Tricine-urea gel electrophoresis showed the normal predicted profile of A␤ peptides without any alterations before or after dimerization from both APP F1 and APP F2 constructs. These findings are consistent with the apparent normal processing of APP GFP fusions used by a number of laboratories (38,(41)(42)(43)(44)(45). However, with this approach, our results unequivocally showed that forced dimerization of APP lowered rather than increased A␤ generation.…”
Section: Discussionsupporting
confidence: 92%
“…Protein concentrations were determined from a calibration curve (Fig. 2D), where we measured the fluorescence intensities of purified CyTEM and YBLIP proteins diluted in HeLa cytoplasmic cell extract, using the confocal microscope setup employed for living cell measurements (14).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative confocal microscopy offers the advantage of revealing spatial information in a nondestructive manner (Sugiyama et al, 2005;Goldsbury et al, 2007;Verveer and Bastiaens, 2008;Wu et al, 2008). This is especially important when dealing with proteins, such as membrane receptors, that are continuously recycled.…”
Section: Bri1 Receptor Density and Biological Significancementioning
confidence: 99%
“…Quantitative methods based on confocal laser scanning microscopy techniques have provided insight in the amount and subcellular localization of proteins (Verveer and Bastiaens, 2008). Confocal imaging is applicable for plant membrane, nuclear, and cytosolic proteins (Mathur, 2007;Berg et al, 2008) and is used in yeast (Wu and Pollard, 2005) and animal cells (Sugiyama et al, 2005;Goldsbury et al, 2007) to quantify fluorescently tagged proteins. In plants, fluorescence-based quantification techniques have been used to determine protein level in whole-tissue samples (Halfhill et al, 2005) and in extracts using ELISA (Richards et al, 2003) or intact cells using flow cytometry (Lu et al, 2007).…”
mentioning
confidence: 99%